THE ROLE OF THE DEPARTMENTS OF WORKERS’ SUPPLY OF DAGESTAN DURING THE GREAT PATRIOTIC WAR - Efendieva, Dzamila Abdulkerimovna (History, Archeology and Ethnography of the Caucasus, 2023)
In the context of efforts to falsify historical facts and underestimate the government’s wartime measures, an examination of the provision of food and industrial goods to the population becomes particularly relevant. The comprehensive exploration of this issue, utilizing Dagestan as a case study, remains incomplete and necessitates further investigation. A thorough analysis of these matters through the lens of labor supply departments enables a more comprehensive understanding of the wartime supply situation for the able-bodied segment of the population. Employing a comparative historical method, this study discusses the intertwined issues of rationed provision, the functioning of the stamp system, and the activities of the Departments of Workers’ Supply (ORS). This approach facilitates an assessment of the effectiveness of the ORS system by comparing quantitative and qualitative indicators of food supply in the republic before and during the war. The principle of historicism enables the tracing of the adaptation process of the working population to the rationed supply system. Utilizing retrospective analysis and synthesizing newly introduced archival documents, this research offers a more exhaustive examination of the various stages in resolving support-related challenges. Special attention is given to the economic situation in Dagestan after the Nazi Germany invasion, emphasizing the food problem and the imperative to transition to a rationed system for supplying food and industrial goods to the population. The ORS system emerges as a key factor in ameliorating the food supply situation for workers, enhancing their nutrition, particularly during night shifts, and aligning the organization of supply with the demands of production.
Keywords: the Great Patriotic War; Dagestan; work supply departments; foodstuff; normalized supply